From Try-On To Buy-On: Augmented Reality (AR)’S Effects on Attitudes and Purchase Intention In Cosmetics - Dewi Fatimah Azzahra; Moira Katja Kabullah Nugraha; Amalia E. Maulana (Green Publisher Indonesia, 2026)
The research investigates how augmented reality (AR) features affect Indonesian consumers' likelihood to buy cosmetics products. The study uses Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze how vividness, interactivity, informativeness, and visual appeal affect consumer perceptions and behaviors based on the Technology Acceptance Model (TAM) and experiential perspectives. The study demonstrates that vividness makes products appear more useful, while interactivity simplifies usage, and visual appeal directly affects consumer attitudes because beauty-related AR experiences heavily rely on aesthetics. The study shows that informativeness has a positive effect, yet it produces less impact than the experiential elements. The combination of perceived usefulness and ease of use leads to more positive consumer attitudes, which prove to be the leading factor in purchase intention. The research expands TAM by adding experiential and aesthetic elements, which helps explain technology adoption processes in hedonic settings. The research demonstrates to practitioners that AR application success depends on creating interfaces that unite user-friendly design with engaging visual elements to boost customer involvement and drive sales and customer retention.